Sustainability and piety - Omer, Spahic (IIUMToday, 2019)
Sustainability in architecture is possible only when there is sustainability in values and philosophies that underpin the former, giving it its identity, vigor and direction. Moreover, sustainability in architecture is possible only when there is sustainability in people’s intellectual, spiritual and moral predilections whereby the philosophies and values of a sustainable architecture are one and the same as those personified by people: the conceivers, patrons, creators and users of architecture. It is for this reason that Koca Mimar Sinan, the chief architect of the Ottoman golden age, said that architecture is at once an estimable and the most difficult calling, and he who would practice it correctly and justly must, above all things, be pious. Muhammad Iqbal on that score while eulogizing the Mosque of Cordova in Spain in a masterpiece poem that carries the same name -- or Masjid-e Qurtaba in Urdu -- uses the beauty and glory of one of the most famous architectural masterpieces in Islamic history as a prism through which he analyzes the nature and some of the most prominent traits of a true believer. At the end of his poem, after describing the underlining qualities both of the Mosque and true believers, and what type of a spiritual affiliation ought to exist between the two, Muhammad Iqbal calls for revolution and reform across the spectrum of the Muslim cultural and civilizational presence. The importance of reforming and sustaining individuals, traditions, systems and institutions, in the context of reminiscing about the Mosque of Cordova and Islamic civilization’s lost repute and luminosity, is readily apparent in the poem.